2022
DOI: 10.18421/tem111-57
|View full text |Cite
|
Sign up to set email alerts
|

IT Blueprint for an Effective Online Learning System with a Blended Approach for Upper Secondary Education System During COVID-19 Pandemic

Abstract: Online learning is becoming the main teaching method since the COVID-19 pandemic. What happens after the pandemic is over? Will the online education be still going? The schools have implemented online learning systems to replace the current teaching methods to ensure the teaching and learning process keeps going. However, research have found that not all students respond well to fully online learning methods, therefore a blended learning system is needed to facilitate the difference in student performance. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Through this framework, instructors can create instructional designs as a way to design and develop online instructional content ( Affouneh et al, 2020 ; Paul et al, 2023 ), while also creating opportunities for student learning and instructor interaction A recent study showed that the COVID-19 period ( Joy, 2020 ) was guided by this framework to achieve instructional purpose and content development that facilitated students' learning experiences. This suggests that for OFA, it may be a useful pedagogical practice for teachers to try to effectively manage student learning by providing a convenient, fast, and friendly learning environment through an online teaching platform/tool interface ( Ramadhan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Through this framework, instructors can create instructional designs as a way to design and develop online instructional content ( Affouneh et al, 2020 ; Paul et al, 2023 ), while also creating opportunities for student learning and instructor interaction A recent study showed that the COVID-19 period ( Joy, 2020 ) was guided by this framework to achieve instructional purpose and content development that facilitated students' learning experiences. This suggests that for OFA, it may be a useful pedagogical practice for teachers to try to effectively manage student learning by providing a convenient, fast, and friendly learning environment through an online teaching platform/tool interface ( Ramadhan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%